Bagaimana Seniman Bali Berkreatifitas Pada Ajang PKB 2021 Dalam Situasi Covid ? - Ni Komang Sri Wahyuni; I Kt. Suteja (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2021)
The Bali Arts festival ini 2021 is starting to rise again in a different form, the 43rd PKB as a forum for artists’ creativity was held virtually, due to the fluctuating covid-19 pandemic in Bali. The creativity produced by the artists is focused and contextual in translating the PKB theme “Purna Jiwa, Prananing Wana Kerthi” or “Plenary Soul, the breath of life. Staging is done virtually and only a few are done offline with the implementation of health protocols. The phenomenon of covid-19 is very motivating for innovation and the spirit of Balinese artists, this can be seen from the appearance of the works which on averageare very interesting. There are 2 (two) interesting works to discuss, namely, the Kreasi Kekebyaran Mimba neem creation dance from the Denpasar city ambassador and the Classical Arja Perfomance from the Singapadu Suara Kanti, Gianyar. The method used in this research is to use qualitative research methods which emphasize more on the quality side of the entity under study. Using qualitative research methods to make it easier to criticize things that exist in the Kreasi Kekebyaran Mimba neem dance performance and gthe Classical Arja Performance both in terms of technique, form, uniqueness and taste, as well as interpreting the values contained in the work. The Kreasi Kekebyaran Mimba neem dance depicts the balance of masculine and feminine symbols in one dancer’s character, this concept is inspired by the Intaran leaf and the Ardhanareswari concept. Classical Arja performance from the Suara Kanti Studio with the title “Taru Urip” which tells the story of matchmaking through the Urip dance given by Galuh Daha which was later won by Prabhu Jenggala, Raden Dharma Sentana. Keywords: PKB, Covid, Kreatifitas, Seniman